2017
DOI: 10.1039/c6ta07864h
|View full text |Cite
|
Sign up to set email alerts
|

Effective strategies for stabilizing sulfur for advanced lithium–sulfur batteries

Abstract: This review focuses on recent developments in the last three years of various sulfur integration methods in lithium-sulfur batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(75 citation statements)
references
References 125 publications
0
74
0
Order By: Relevance
“…Particularly, a crucial characteristic of LSBs is that S 8 molecules can bind two Li atoms per S atom [S 8 +16Li↔8Li 2 S] . Thus, compared to other cathode materials, the energy density and electrochemical performance of sulfur electrode can be significantly improved . In addition, sulfur is cheap, non‐toxicity, naturally abundant, and environmentally benign …”
Section: Introductionmentioning
confidence: 99%
“…Particularly, a crucial characteristic of LSBs is that S 8 molecules can bind two Li atoms per S atom [S 8 +16Li↔8Li 2 S] . Thus, compared to other cathode materials, the energy density and electrochemical performance of sulfur electrode can be significantly improved . In addition, sulfur is cheap, non‐toxicity, naturally abundant, and environmentally benign …”
Section: Introductionmentioning
confidence: 99%
“…Directed by the same research group, trace amounts of water (25-50 ppm) were also found to play a similar role as Cs + and were introduced as electrolyte additives to control the morphology [344]. They found that the trace amount of HF formed from the side reactions of LiPF 6 and H 2 O can facilitate the formation of uniform and dense LiF-rich SEI layers on the substrate. Such LiFrich SEI layers aid the uniform distribution of the electric field and thus lead to Li nanorod arrays aligned vertically to the substrate.…”
Section: Morphology Controlmentioning
confidence: 98%
“…Unfortunately, state-of-theart LIBs based on insertion-type transition metals/metal oxides cannot deliver enough energy density to meet the increasing demands of long-range electric vehicles [2][3][4]. Hence, it is of significance to search for new electrode materials which possess low molecular/atomic weight and are capable of multi-ion/-electron transfers per molecule/ atom [3,[5][6][7][8][9][10]. As one of the most abundant elements in the earth's crust, sulfur possesses a relatively low atomic weight of 32 g mol −1 and is a cost-effective and environmental friendly alternative to tradition LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the insulating nature of sulfur and the dissolution of lithium polysulfides in organic electrolytes limit the practical application of Li–S batteries . Therefore, to solve the above problems, previous studies of Li–S batteries focused on developing advanced host materials for sulfur, including carbon nanotubes, graphene, porous carbon, metal oxides, covalent organic framework (COFs), metal–organic frameworks (MOFs), polymers, and others . Although significant improvements in discharge capacity and long‐cycling performance of Li–S batteries have been achieved, the complex preparation and the high cost of these host materials remain a challenge…”
Section: Introductionmentioning
confidence: 99%